Burn wound healing activity of ethanol extract gel of Green Algae (Ulva lactuca L) in mice - Wahyu Widyaningsih; Sapto Yuliani; Vivi Sofia; Reka Rukmiati; Khozanatul Ulwy (Pharmaciana, 2022)
Recently, burn injuries have become a major cause of morbidity and mortality in low-middle-income countries. Burn injuries are tissue loss caused by contact with heat sources such as hot water, fire, chemicals, electricity, and radiation. According to the WHO Global Burden Disease, in 2017 an estimated 180.000 people died from burn injuries. Ethanol extract of green algae (EEGA) contains compounds that potentially heal burn injuries. The research was conducted to obtain a gel formulation from EEGA and test its burn wound healing properties in mice (Mus musculus). Forty-five mice were divided into five groups: I (negative control), II (treated with gel base), III (positive control, Bioplacenton gel), IV (5% EEGA gel), and V (10% EEGA gel). Wound diameters and description scores were observed every fourth, seventh, and fourteenth day, and the derived data were analyzed in the SPSS program with the one-way analysis of variance (ANOVA) and least significance difference (LSD) test. The results indicate that EEGA can be formulated into gels with physical properties compliant with the requirements of the dosage form. Further, it was found that Groups IV and V showed significant reductions in wound description scores and diameters (p<0.05). In conclusion, gels containing 5% and 10% EEGA possess burn wound healing properties.